Epoxy-based composites reinforced with African teff straw (Eragrostis tef) for lightweight applications. Issue 4 (May 2019) - Devnani, GL; Sinha, Shishir
The objective of this work is to access the possibility of reinforcement of a new and almost inexpensive natural fiber in epoxy composites. In this study, epoxy-based composites reinforced with African teff straw ( Eragrostis tef) have been fabricated using simple hand layup technique with different fiber loadings varying from 5% to 25%. The fiber surface is treated with 5% alkali, 10% alkali, silane, and acetic anhydride to improve the interaction between fiber and matrix. The mechanical, morphological, water absorption, and thermal characteristics of both the untreated and the treated composites have been studied to analyze the properties and effect of surface treatment on prepared composites. Water diffusion mechanism has also been studied. The effect of various treatment methodologies has been compared to obtain superior quality composites; 15% fiber loading and silane treatment have improved the tensile strength and flexural strength by 40% and 25%, respectively, while 5% alkali-treated composites increased tensile strength by 12% as compared to neat epoxy resin.